Aromatic plants: a source of phenolic compounds? - Oliveira, A.S. (2017)
Nowadays there is a renaissance of the interest in aromatic plants due to their properties, specially their antioxidant properties. The antioxidant activity of the aromatic plants is mainly due to the high content of phenolic acids (gallic acid, protocatechuic acid, caffeic acid and rosmarinic acid), flavonoids (quercetin), phenolic diterpenes (carnosol and carnosic acid) and volatile oils (eugenol, carvacrol and thymol). The food industry has demonstrated an increasing interest in phenolic compounds to prevent the oxidative degradation of lipids and to improve the quality and nutritional value of the food and thus increasing the shelf life of food products. The aim of this study is to compare aromatic plants commonly used for culinary purposes in what regards to their composition in phenolic compounds.